2000
DOI: 10.1152/jappl.2000.89.2.458
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient secretion of atrial natriuretic peptide at acute phase of myocardial infarction

Abstract: To investigate the secretion of the plasma levels of atrial natriuretic peptide (ANP) in patients with acute myocardial infarction (AMI), we evaluated the relationship between plasma levels of ANP and pulmonary capillary wedge pressure (PCWP) in 45 consecutive patients during the acute phase of AMI ( approximately 12 h after the attack) (group 1) and compared data with those obtained after 1 mo (group 2). In both groups 1 and 2, plasma ANP levels significantly correlated with PCWP. The slope of the linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Regulation of the synthesis and release of ANP and BNP has been reported to differ 32–34 . Plasma ANP is increased immediately but plasma BNP is slowly increased as a consequence of hemodynamic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of the synthesis and release of ANP and BNP has been reported to differ 32–34 . Plasma ANP is increased immediately but plasma BNP is slowly increased as a consequence of hemodynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ANP is increased immediately but plasma BNP is slowly increased as a consequence of hemodynamic changes. Maeda et al 32 showed that LVEDP and ANP concentrations were significantly increased from baseline 30 minutes after acute myocardial infarction. However, despite persistently high LVEDP after 180 minutes, ANP concentrations decreased significantly to 63% of the peak level.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs with MMVD, CBs, other than plasma ANP and NT-proANP concentrations, have clinical utility include plasma N-terminal pro-brain natriuretic peptide (NT-proBNP) and cardiac troponin I (cTnI) concentrations [ 14 , 16 , 33 , 34 ]. NT-proBNP is released into the blood circulation primarily in response to ventricular myocyte stretch, and cTnI is released into the blood with cardiomyocyte injury.…”
mentioning
confidence: 99%
“…Although the role of cardiac NEP in the repair of infarcted myocardium is not clear, the natriuretic pep‐tide and/or kinin system may be involved through this up‐regulation, since NEP is responsible for the breakdown of ANP/BNP and BK. Thus, the increased NEP activity in the infarcted area would reduce not only ANP concentrations (7) but also BK levels. However, we found an increase of myocardial BK levels in infracted areas of untreated rats, indicating that kinin concentrations in the myocardium are partially determined by factors other than kinin‐degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…BK was quantitated by a specific RIA, as described previously (6). The antiserum displayed a 36% cross-reactivity to T-kinin and had no affinity to smaller kinin fragments such as [1][2][3][4][5][6][7][8]…”
Section: Measurement Of Bradykinin Concentrationsmentioning
confidence: 99%